Dementia and mild cognitive impairment in China: From the public health perspective. (31st December 2021) - Jia, Jianping; Jia, Longfei; Du, Yifeng; Chu, Lan; Zhang, Zhanjun; Quan, Meina; Wei, Cuibai; Li, Fangyu; Fu, Yue; Tang, Yi; Lyu, Diyang; Li, Yan; et al.
Abstract: Background: China has the largest population of patients with dementia and mild cognitive impairment (MCI) in the world, imposing a heavy burden on the public and healthcare systems. The major concerns from the public health perspective include: prevalence, health economic burden, risk factors, and management strategy. Method: Statistical analyses were performed on the largest and most comprehensive dementia and MCI cohort study (fig. 1) in China. Systemic review was also done on the studies from the past 10 years. Result: For the prevalence, our data showed that, the overall prevalence of dementia was 6.0% and of MCI was 15.5%. This represented 15.07 million individuals with dementia and 38.77 million individuals with MCI (fig. 2). For the health economic burden, our systematic review showed that the annual total costs associated with dementia would be 248.71 billion in 2020, 507·49 billion in 2030, 1·00 trillion in 2040, and 1·89 trillion in 2050 in China; on a global scale, these costs would be 1·33 trillion in 2020, 2·54 trillion in 2030, 4·83 trillion in 2040, and 9·12 trillion in 2050 (fig. 3). For the risk factors, our study found that MCI and dementia shared 9 similar, modifiable risk factors, including rural residence, fewer years of education, living alone, smoking, hypertension, hyperlipidaemia, diabetes, and heart and cerebrovascular disease. Conclusion: The above public health data indicated that dementia and MCI population has become a heavy burden not only in China but around the world, which called for us to develop systematic management strategies, including: 1) prevention strategy targeting the MCI population by controlling for the modifiable risk factors and increasing public awareness; 2) monitoring strategy for all people with MCI by anti‐dementia national surveillance network that does regular cognitive evaluation and training; 3) early diagnosis and treatment strategy for people with dementia by trained dementia professionals; 4) care strategy by an integrative dementia nursing system. These strategies would form the infrastructure that effectively control the prevalence of dementia in China.